Él Code-Switches More Than tú y yo: New Data for the Subject Pronoun-Verb Switch Constraint - Bellamy, Kate; Stadthagen-Gonzalez, Hans; Parafita Couto, M. Carmen (Languages (Basel), 2022)
In early studies, code-switches between a subject pronoun and a finite verb were considered highly dispreferred or even impossible. However, naturalistic data from several language pairs has since highlighted that such switches are possible, although their grammaticality is constrained by the typology of the pronouns involved. In this study, we test the switching constraints postulated for subject pronouns-verbs among P’urhepecha-Spanish bilinguals (n = 12) from Michoacán, western Mexico. Using a two-alternative forced-choice acceptability judgement task (2AFC), we found that, contrary to expectations, switches between a third person singular pronoun and a verb were considered the most acceptable, followed by the coordinated ‘you and I’ second person, then the first person singular. The same order was found for both switch directions, despite third-person pronouns in P’urhepecha having a stronger typological profile. Building on the results of previous studies, we suggest that the lack of preference for a single switch direction is evidence for language-specific code-switching patterns, as well as possible differences in productive vs. receptive language. Additionally, we highlight the probative value of judgement data, particularly those emerging from 2AFC tasks, as a means of expanding our understanding of grammaticality in code-switching.